(untitled) (International Journal of Technology and Management Research, 2020)
Over the last decade, Ghana and South Africa have been among some African countries that have become more entrenched in foreign direct investment (FDI). The past quarter of the century has witnessed a remarkable growth in world foreign direct investment flows, coupled with the evolving investment strategies of national policies globally. This paper examines and compares the legislative frameworks and regulatory policies governing FDIs in South Africa and Ghana and the hurdles that need to be overcome to ensure smooth implementation of these policies. This has become evident in their current enactment of their regulations with the object of promoting investments in these economies. However, these jurisdictions have restrictions placed on their regulations; hence, putting frustrations on foreign direct investments. It appears that although in terms of overall statutory FDI regulations, African countries are on the average not more restrictive than other developing nations, some of these countries have obstacles that are both severe and restrictive such as land ownership, whether discriminatory or general in nature, act as an important deterrent to foreign investment. This discussion would focus on comparing restrictions imposed by legislation or policies affecting Soith Africa anf Ghana with regards to foreign direct investment. And disputes that emerge due to the restrictions among the jurisdictions. Keywords: Foreign Direct Investment, Economic Growth, International Law, Legislative Framework, Regulatory Bodies, Bilateral Investment Treaties.